1998
DOI: 10.1136/jmg.35.3.222
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of chromosomally normal livebirths with increased fetal nuchal translucency at 10-14 weeks' gestation.

Abstract: The aim ofthis study was to determine the outcome of chromosomally normal livebirths with increased fetal nuchal translucency at 10-14 weeks' gestation. Clinical follow up of 89 chromosomally normal livebirths that in fetal life had a miniimum nuchal translucency thickness of 3.5 mm and a comparison group of 302 infants whose fetal nuchal translucency thickness at 10-14 weeks of gestation was less than 3.5 mm was performed. Major abnormalities, mainly structural defects of the cardiovascular or skeletal system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
57
0
10

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 20 publications
5
57
0
10
Order By: Relevance
“…In chromosomally normal fetuses, increased NT is associated with a wide range of fetal defects and genetic syndromes 5,12 . In addition, increased NT may also be a marker that predicts postnatal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In chromosomally normal fetuses, increased NT is associated with a wide range of fetal defects and genetic syndromes 5,12 . In addition, increased NT may also be a marker that predicts postnatal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…As genetic syndromes are diagnosed in around 5% of the fetuses, additional investigations should be considered (Bilardo et al, 2007). Noonan syndrome is the most frequently reported genetic syndrome in association with an increased NT, with a prenatal incidence ranging between 1 and 3% (Brady et al, 1998;Souka et al, 1998;Hiippala et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Choice a fetal NT cut-off point to define an increased fetal NT thickness is very important in the prenatal care program because when NT levels increase, the chance that healthy baby will be decrease [19,21,22]. Many studies reported: the threshold of fixed 2.5mm cut-off point and 95th percentile depending cut-off were used effectively as an increased fetal NT thickness for screening trisomy 21 with the varied detection rate from 75% to 91% and the varied false positive rate from 1% to 5.4% [6,14,16,17,23,24].…”
Section: Discussionmentioning
confidence: 99%